ʺPortfolio as an innovative tool for assessing individual achievements of students and a way to self-motivation in adaptive learningʺ - Skorokhodova, I. (Problems of Engineer-Pedagogical Education, 2024)
The system of assessment of students' learning achievements, as well as the social institution of education itself, has recently undergone significant changes and transformations. The main one is the global transformation of approaches to assessing student achievement. If earlier the main focus of assessment was on the volume and quality of theoretical knowledge accumulated by the student, in today's realities this is no longer an effective factor. What matters now is not the amount of theoretical material accumulated by the student, but the ability to use it creatively, efficiently and effectively, both in the profession and in life in general. The article considers the concepts of educational portfolio and portfolio of an education applicant, identifies the advantages and disadvantages of using a portfolio, summarises the algorithm and stages of portfolio formation, defines the structure and develops the main sections of the portfolio. The feasibility of introducing a portfolio as an innovative way to assess the achievements of educational institutions is analysed. A portfolio in education is a tool for collecting, evaluating and displaying the achievements of students. It may include academic results, projects, creative works, teacher feedback and supporting materials. It is important for an applicant to have a high-quality and meaningful portfolio to stand out among other candidates when applying and throughout their studies. Subsequently, it is successfully used to find a professional path through specialised training and enter the labour market. Portfolios allow students to demonstrate their teamwork, creativity, independent work and other skills that cannot always be measured by standardised tests. It also stimulates learners' self-motivation by allowing them to see their progress and achievements. Adaptive learning involves individualising the learning process, including the pace and methods that meet the needs of each student. The use of portfolios allows teachers to track the personal progress of each student and use this information to develop a more individualised curriculum. Provide feedback and support to students in their studies.